Lipase Catalyzed Synthesis of Aromatic Esters of Sugar Alcohols - R. Croitoru; L. A. M. van den Broek; A. E. Frissen; C. M. Davidescu; F. Peter; C. G. Boeriu (Communications Earth & Environment, 2011)
Commercially available lipases (Candida antarctica lipase B, Novozyme 435, Thermomyces lanuginosus lipase, and Lipozyme TL IM), as well as sol-gel immobilized lipases, have been screened for their ability to acylate regioselectively xylitol, sorbitol, and mannitol with a phenolic ester in a binary mixture of t-butanol and dimethylsulfoxide. HPLC and MALDI-TOF MS analysis revealed the exclusive formation of monoesters for all studied sugar alcohols. The lipases immobilized by the sol-gel entrapment method proved to be efficient catalysts, leading to high conversions (up to 60%) in the investigated acylation reactions. From a sequence of silane precursors with different nonhydrolyzable groups in their structure, the presence of octyl and i-butyl group was most beneficial for the catalytic activity of sol-gel entrapped lipases in the studied process.